Towards the automated synthesis of artemisinin at low temperature - Herron, James John (2023)
According to the World Health Organisation (WHO) there were an estimated 228 million cases of malaria worldwide in 2018, resulting in 405,000 deaths, the majority of which occur in the most underdeveloped regions in the world.1 Since 2002, Artemisinin-based combination therapies (ACTs) have been designated as the first-line antimalarial treatment by the WHO, and despite the development of the first-generation RTS,S/AS01 vaccine in 2021, ACTs remain the most viable treatment of malaria.2–4 There is, therefore, a great necessity for a substantial and reliable delivery of affordable artemisinin.1 Since industrial production of artemisinin was developed by Sanofi in 2013, investigations have been made to improve the synthesis, with the ultimate aim of reducing the cost of this crucial drug.5 A crucial step in this synthesis is the reaction of the precursor, dihydroartemisinic acid (DHAA), with singlet oxygen (1O2). The reaction can be conducted using photochemically generated 1O2 to produce several hydroperoxide intermediates, of which it is generally accepted that only one can form artemisinin.5–9 The reduction of the photo-oxidative temperature can lead to increased selectivity towards the desired hydroperoxide.8 Herein, this Thesis describes the development of a continuous flow reactor capable of conducting reactions at -80°C, to further exploit increases in selectivity of the photo-oxidation. The reactor was then adapted to perform the continuous synthesis of artemisinin which was simultaneously developed with ‘On-line’ HPLC-UV and -ELSD (evaporative light scattering detector) analysis to produce an automated flow reactor. Chapter 2 details modifications to a prototype photochemical reactor previously built at Nottingham. Ultimately, a minimum interior reactor temperature of -46°C was achieved, resulting in improvements to the selectivity of the photo-oxidation of DHAA. Chapter 3 presents the further development of a second reactor capable of conducting reactions down to -80°C, resulting in further improvements in photo-oxidative selectivity. The reactor was then employed to perform the semi-synthesis of artemisinin using continuous ‘one-pot’ and semi-continuous ‘two-pot’ regimes. Through simultaneous reactor and reaction development, the enhancements at low temperature were found to translate to improved yields of artemisinin at -80°C, achieving a highest yield of 68 %. Chapter 4 explores further adaptations to facilitate automated reactions. This required establishing a method for ‘On-line’ analysis that exhibits high accuracy, precision and sufficient dynamic range. Modifications to the reactor were also needed to implement a reliable sampling of the liquid-gas mixture. HPLC-UV and -ELSD were selected as the methods of analysis. The use of the dual ‘On-line’ detection combined with automatic sampling provided valuable data verification and insights into the formation of artemisinin; showing that the conversion of the hydroperoxide to artemisinin occur slowly and required adaptation to the reactor, including the addition of a Vortex reactor, to improve the formation of artemisinin. The implementation of a low temperature, biphasic, multi-step synthesis into an automated system, provided numerous challenges. However, through iterative reactor development the automated syntheses of artemisinin and rose oxide were performed, showcasing the ability of the system and the self-optimisation framework to conduct computer controlled reactions. These experiments highlighted the potential for further advancements, both in reactor design and the self-optimisation framework, to enable the efficient implementation of fully self-optimised systems. Chapter 5 outlines the experimental work carried out within this Thesis, including HPLC method development for the quantification of photochemically synthesised artemisinin and rose oxide. Many challenges were encountered in the development of the method for artemisinin detection, primarily due to large fluctuations in the sensitivity of the ELSD. Eventually, HPLC-UV was made the primary method for quantitative analysis, while ELSD was used to gather additional information into the composition of the photoproduct. Finally, Chapter 6 summaries the work described in this Thesis and examines the success of the approaches with respect to the initial aims. A summary of future works is also presented.